Suicide or accident? A psychological autopsy study of suicide in youths under the age of 16 compared to deaths labeled as accidents - Freuchen Anne; Kjelsberg Ellen; Grøholt Berit (BMC, 2012)
Abstract Objective In the present paper, we describe suicide in youths under 16 years of age and compare their risk factors for suicide to those of older adolescents as described in the literature. Furthermore, we evaluate the possible mislabeling of suicides as accidents, and vice versa. Method We used the data from a nationwide psychological autopsy of youths 15 years and younger who had committed suicide or died in accidents in Norway from 1993 to 2004 (n = 84). We additionally constructed a suicide index to distinguish between the two causes of death. Results The young suicide victims presented, with little gender difference, fewer obvious risk factors and less suicide intent than commonly described for older adolescents. The suicide index distinguished quite well between suicides and accidents, with few cases indicating a possible mislabeling, although some suicide cases could have been labeled as uncertain. Conclusion In line with previous research, suicides in 11-15-year-olds have many similarities to suicides in older adolescents in terms of external circumstances, but they present less apparent warning signs. In our total sample of 84 deaths, there were few indications of incorrect labeling.